Statistical Considerations in Clinical Trial Design of Immunotherapeutic Cancer Agents. Issue 7 (September 2015) - Dranitsaris, George; Cohen, Roger B.; Acton, Gary; Keltner, Llew; Price, Melissa; Amir, Eitan; Podack, Eckhard R.; Schreiber, Taylor H.
Abstract : The classical model for identification and clinical development of anticancer agents was based on small molecules, which were often quite toxic. Early studies in small groups of patients would seek to identify a maximum tolerated dose and major dose-limiting toxicities. Tumor response (shrinkage) would be assessed after a minimum number of doses in phase II testing. The decision to take the drug into the randomized phase III clinical setting was usually based on the proportion and duration of objective tumor responses, along with overall survival compared with historical controls. Immune-oncologics that are designed to fight cancer by direct CD8 + T-cell priming and activation or by blocking a negative regulatory molecule have a number of sharp distinctions from cytotoxic drugs. These include cytoreductive effects that may be very different in timing of onset from traditional chemotherapy and the potential for inducing long-term durable remissions even in heavily pretreated patients with metastatic disease. In this paper we review the different classes of immune-oncologic drugs in clinical development with particular attention to the biostatistical challenges associated with evaluating efficacy in clinical trials. Confronting these issues upfront is particularly important given the rapidly expanding number of clinical trials with both monotherapy and combination trials in immunooncology.